Outcome of Microsurgical Varicocelectomy: A One-Year Single-Center Study in a Secondary Hospital in West Java, Indonesia - P. Wajdi, Rifki; Putra, Rosadi (Jurnal Locus Penelitian dan Pengabdian, 2025)
Varicoceles, characterized by the dilation of veins in the pampiniform plexus, represent a common etiology of male-factor infertility. Despite various available treatment modalities, the optimal approach for varicocele management remains a subject of debate. Surgical interventions, including open, laparoscopic, and microscopic techniques, are among the therapeutic options. Here, we present our initial experience with microsurgical varicocelectomy, delineating the clinical features and assessing the outcomes of this approach in a secondary healthcare setting in Indonesia. This retrospective study was conducted from April 2022 to April 2023, involving 53 patients diagnosed with symptomatic varicoceles. All patients underwent varicocelectomy using microsurgical techniques. Patient medical records were retrospectively reviewed to document demographic characteristics, preoperative physical examinations and presenting complaints, laboratory findings, including sperm analysis results, varicocele location, and postoperative outcomes. A total of 53 study participants, with a mean age of 35.74 ± 7.27 years, were enrolled. Testicular pain was the primary presenting complaint in 73.6% of cases. Bilateral varicoceles were observed in 64.2% of cases. Pre-intervention semen analysis was conducted in 24 patients, revealing oligoasthenoteratozoospermia in the majority (50.0%), with only 2 samples exhibiting normal parameters. Following surgery, semen analysis was repeated in 16 patients, with 31.3% showing normal results. In the postoperative period, all patients reporting testicular pain experienced relief, while 35.7% (5/14) of previously infertile patients successfully impregnated their partners. Microsurgical varicocelectomy proves to be an effective intervention for symptomatic varicoceles, leading to enhanced fertility outcomes and alleviation of pain.